PERANAN AUDIT OPRASIONAL DALAM MENINGKATKAN EFEKTIVITAS DAN EFISIENSI SYSTEM PENJUALAN PADA PERUSAHAAN PT. ANDALAN FINANCE - Rohmatin, Rohmatin; Widiastoeti, Hendy (Universitas 17 Agustus 1945 Surabaya, 2018)
ABSTRACTBased on the test results and a discussion of the operational audit role in improving the effectiveness and efficiency of the sales system in PT. Mainstay of Finance, the researchers can summarize that the effectiveness and efficiency of sales amounted to 96.00%, the value can answer the problem formulation and may imply that the sales activity in the mainstay Finance